PENYULUHAN DAN PELAYANAN KESEHATAN TERNAK SAPI DI DESA APUAN KECAMATAN SUSUT KABUPATEN BANGLI - I K. Berata; I W. Sudira1; I P. Suastika; N K. Suwiti; N. Suparta (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2013)
This Community Service was conducted on June 8th, 2013 in Apuan village, Bangli regency in the form ofsocialization and healthy service for the bali cattle. The aim of this program was to give knowledge to the farmersand healthy examination for their cattles.This programe was held by visiting the farmers or door to door method.Amount 107 farmers were visited and there were 212 cattle were examined for their healthy. Many kind ofdiseases were suffered at their cattle among others helminthiasis = 19 cases (8,96%) and infectious diseases = 13cases (6,13%). The other cattle showed anemia may be caused by anorexia, etc. The conclusion of this programis all of the farmers were interested to attend the socialization and healthy service for their cattle.